Data acquisition and study of He spectrum under electric and magnetic fields - Shobahani, M.; Mofiz, U. A. (BRAC University, 2014)
Data acquisition system for the spectrum of ionized gases is developed and the spectrum of He gas under electric and magnetic fields are studied. The results are shown through captured photographs, which shows that the spectrums are shifted and their intensities varies with the increasing intensity of the electric and magnetic fields.